Effects of Levothyroxine Replacement Therapy on Parameters of Metabolic Syndrome and Atherosclerosis in Hypothyroid Patients: A Prospective Pilot Study - Zoran Gluvic; Emina Sudar; Jelena Tica; Aleksandra Jovanovic; Sonja Zafirovic; Ratko Tomasevic; Esma R. Isenovic (International Journal of Endocrinology)
The aim of this study was to investigate the effect of levothyroxine (LT4) replacement therapy during three months on some parameters of metabolic syndrome and atherosclerosis in patients with increased thyroid-stimulating hormone (TSH) level. This study included a group of 30 female patients with TSH level >4 mIU/L and 15 matched healthy controls. Intima media complex thickness (IMCT) and peak systolic flow velocity (PSFV) of superficial femoral artery were determined by Color Doppler scan. In hypothyroid subjects, BMI, SBP, DBP, and TSH were significantly increased versus controls and decreased after LT4 administration. FT4 was significantly lower in hypothyroid subjects compared with controls and significantly higher by treatment. TC, Tg, HDL-C, and LDL-C were similar to controls at baseline but TC and LDL-C were significantly decreased by LH4 treatment. IMCT was significantly increased versus controls at baseline and significantly reduced by treatment. PSFV was similar to controls at baseline and significantly decreased on treatment. In this study, we have demonstrated the effects of LT4 replacement therapy during three months of treatment on correction of risk factors of metabolic syndrome and atherosclerosis.